Integration of amyloid-β oligomerization tendency as a plasma biomarker in Alzheimer's disease diagnosis - Pyun, Jung-Min; Youn, Young Chul; Park, Young Ho; Kim, SangYun (Frontiers in Neurology, 2023)
INTRODUCTION: There has been significant development in blood-based biomarkers targeting amyloidopathy of Alzheimer’s disease (AD). However, guidelines for integrating such biomarkers into AD diagnosis are still inadequate. Multimer Detection System-Oligomeric Amyloid-β (MDS-OAβ) as a plasma biomarker detecting oligomerization tendency is available in clinical practice. MAIN TEXT: We suggest how to interpret results of plasma biomarker for amyloidopathy using MDS-OAβ with neuropsychological test, brain MRI, and amyloid PET for AD diagnosis. Combination of each test result differentiates various stages of AD, other neurodegenerative diseases, or cognitive impairment due to causes other than neurodegeneration. DISCUSSION: A systematic interpretation strategy could support accurate diagnosis and staging of AD. Moreover, comprehensive use of biomarkers which target amyloidopathy such as amyloid PET on brain amyloid plaque and MDS-OAβ on amyloid-β oligomerization tendency can complement to gain advanced insights of amyloid-β dynamics in AD.